The Asthma Family Tree: Evaluating Associations Between Childhood, Parental, and Grandparental Asthma in Seven Chinese Cities - Yu, Hongyao; Su, Fan; Wang, Le-Bing; Hemminki, Kari; Dharmage, Shyamali C.; Bowatte, Gayan; Bui, Dinh; Qian, Zhengmin; Vaughn, Michael G.; Aaron, Hannah E.; Xiong, Shimin; Shen, Xubo; et al. (Frontiers in Pediatrics, 2021)
Objective: To evaluate the associations between childhood, parental, and grandparental asthma. Methods: We studied 59484 children randomly selected from 94 kindergartens, elementary, and middle schools in seven Chinese cities from 2012 to 2013, using a cross-sectional survey-based study design. Information on their and their family members’ (parents, paternal grandparents and maternal grandparents) asthma status were reported by children’s parents or guardians. Mixed effects logistic regressions were used to assess hereditary patterns of asthma and mediation analysis was performed to estimate the potential mediation effect of parents on the association between grandparental asthma and childhood asthma. Results: The magnitude of ORs for childhood asthma increased as the number of family members affected by asthma increased. Among children who had one family member with asthma, childhood asthma was associated with asthma in maternal grandmothers (OR: 2.08, 95% CI: 1.67-2.59), maternal grandfathers (OR: 2.08, 95% CI: 1.71-2.53), paternal grandmothers (OR: 2.40, 95% CI: 1.93-2.99), and paternal grandfathers (OR: 2.59, 95% CI: 2.14-3.13). Among children who had two family members with asthma, the highest asthma risk was found when both parents had asthma (OR: 15.92, 95% CI: 4.66-54.45). Parents had a small proportion of mediation effect (9%-12%) on the association between grandparental asthma and childhood asthma. Conclusions: Grandparents with asthma were associated with childhood asthma and parents with asthma partially mediated the association.